Profiling of amines in biological samples using polythioester-functionalized magnetic nanoprobe - Qiu, Yuming; Zhang, Mo; Lai, Zhizhen; Zhang, Renjun; Tian, Hongtao; Liu, Shuai; Li, Dan; Zhou, Jiang; Li, Zhili (Frontiers in Bioengineering and Biotechnology, 2023)
The metabolic balance of amines is closely related to human health. It remains a great challenge to analyze amines with high-throughput and high-coverage. Here, polythioester-functionalized magnetic nanoprobes (PMPs) have been prepared under mild conditions and applied in chemoselective capture of amides. With the introduction of polythioester, PMPs demonstrate remarkably increased capture efficiency, leading to the dramatically improved sensitivity of mass spectrometry detection. The analysis method with PMPs treatment has been applied in rapid detection of more than 100 amines in lung adenocarcinoma cell lines, mouse organ tissues, and 103 human serum samples with high-throughput and high-coverage. Statistical analysis shows that arginine biosynthesis differed between lung adenocarcinoma cell lines. Phenylalanine, tyrosine and tryptophan biosynthesis differed between tissues. The combination indicators demonstrate a great diagnostic accuracy for distinguishing between health and lung disease subjects as well as differentiating the patients with benign lung disease and lung cancer. With powerful capture ability, low-cost preparation, and convenient separation, the PMPs demonstrate promising application in the intensive study of metabolic pathways and early diagnosis of disease.